THE PORTRAIT OF DYSTOPIA SOCIETY IN FLAWED NOVEL - Gultom, Eva Solina; Salsabila, Syifa (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This study looks at how control and resistance are portrayed in Cecelia Ahern's dystopian novel Flawed and how the main character reacts to it. The goal of this study is to examine the concepts of control and resistance as they are presented in the book Flawed. Michel Foucault's theory of power and knowledge was applied to this study. The descriptive qualitative approach was used to carry out this study. The researcher discovered sixteen data sets with resistance elements from Celestine as the main character and fourteen data sets with control aspects from the government. The research's conclusions demonstrate how the government exercises its authority and existence through various means of control, including prohibitions, surveillance, and retaliation against the Flawed (opponents). Contrary to this, Celestine's resistance as the major character demonstrates that she typically resists verbally rather than physically. Celestine chooses to rebel and resist this system of control, which inspires a resistance movement and gives hope to those who are suppressed. The resistance carried out by Celestine shows that the power and knowledge held by the government are not absolute.